ANALISIS SWOT DAN REKOMENDASI STRATEGIS UNTUK PENINGKATAN DAYA SAING STUDI KASUS USAHA BAKSO MAS WAHYU - Zainarti Zainarti; Nada Sausan Adha Fili; Afiyah Dwi Astri; Muhammad Alwi Hasibuan (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Abstract. This research aims to increase the competitiveness of the Bakso Mas Wahyu business through SWOT analysis and strategic recommendations. SWOT Analysis (Strengths, Weaknesses, Opportunities, and Threats) With this analysis, companies can find out internal strengths and weaknesses as well as external opportunities and threats that can influence business success. SWOT analysis will help identify four main components that influence the competitiveness of Bakso Mas Wahyu: strengths, weaknesses, opportunities and threats. This research uses a qualitative approach with a case study method to explore it. The case study was chosen because it allows researchers to obtain in-depth and comprehensive information about the Bakso Mas Wahyu business, including the strengths, weaknesses, opportunities and threats it faces. Based on the SWOT analysis and strategic recommendations that have been carried out for the Bakso Mas Wahyu business, it can be concluded that Bakso Mas Wahyu has great potential to continue to grow and develop in the market.